Isolated Central Nervous System Relapse in Chronic Myeloid Leukemia - Juliana Gomez; Victor Duenas (Case Reports in Medicine)
Chronic myeloid leukemia is a myeloproliferative disorder that has three distinguished phases: chronic, accelerated, and blastic. In extremely rare cases, the blast phase can affect the central nervous system without concomitant bone marrow involvement. We report the case of a patient with chronic myeloid leukemia who, despite having achieved complete cytogenetic remission in the bone marrow for several years, experienced a blast crisis of the central nervous system following an episode of infectious meningoencephalitis.